Esensi Isi Atau Materi Pendidikan dalam Perspektif Islam - Lutfia Asyhadi; Atana Ahmil Nahdhiyah; Mila Rif’ati; Mohammad Asrori (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Every science is included in the science that was born from several concepts related to the content or educational material. Conclusion content or material from education science can be arranged in a systematic and structured way through variables and components in education. The discussion in this scientific work relates to the nature of educational material from an Islamic perspective. The purpose of this study is to explain the purpose of educational content or materials from an Islamic point of view using the content analysis study method. In this article it is found that the nature of the Islamic education curriculum can correspond to the nature of human creation which is often referred to as insan al-kamil. Therefore, the substance of education is expected to be able to bridge students in forming personalities that are in accordance with Islamic ideology.